An instructive model of entropy - Zimmerman, Seth (International journal of mathematical education in science and technology, 2010)
This article first notes the misinterpretation of a common thought experiment, and the misleading comment that 'systems tend to flow from less probable to more probable macrostates'. It analyses the experiment, generalizes it and introduces a new tool of investigation, the simplectic structure. A time-symmetric model is built upon this structure, yielding several non-intuitive results. The approach is combinatorial rather than statistical, and assumes that entropy is equivalent to 'missing information'. The intention of this article is not only to present interesting results, but also, by deliberately starting with a simple example and developing it through proof and computer simulation, to clarify the often confusing subject of entropy. The article should be particularly stimulating to students and instructors of discrete mathematics or undergraduate physics.